The effect of psychological skill training program and positive feedback on handball player's self-efficacy beliefs and their shot - KÜÇÜK, VEYSEL (My University, 2022)
Background. Recent research has revealed the importance of psychological skills training and various physiological exercises to improve sporting performance. In light of all these facts, knowing that psychological skills training is necessary to improve sporting performance, and knowing the importance of the psychological performance program to develop these skills and ensure the control and stability of emotions, particularly in adolescence, led to the emergence of this study. Objectives. This study aimed to understand the effect of 10-week psychological skills training and positive feedback on handball players\" self-efficacy beliefs and shot accuracy. Methods. Thirty-eight female handball players aged between 15 and 19 were included in two study groups and one control group. Whereas the first study group received psychological skill training, the second group received planned positive feedback and psychological skills training. The data were collected through a personal information form, a self-efficacy scale (five-point Likert-type scale), and a shot accuracy measurement scale. Then the pretest-posttest controlled group patterned model was used to determine the differences between the groups. GraphPad Prism 8 was used for statistical analysis with the conventional method. Results. 10-week psychological skills training increased the self-efficacy performance of young handball players in both study groups compared to their pretest results (P<0.01), and the increase was significant in study group 2 compared to the control group (P<0.01). The results also showed that the psychological skills training increased the performance of the shot accuracy of the handball players in both study groups compared to their pretest results. Still, the increase was significant in the study group receiving positive feedback (P<0.001). Moreover, the increase in the shot accuracy test performance of the positive feedback-receiving group was higher than the control and non-receiving group (P<0.01 and P<0.001, respectively). Conclusion. In conclusion, this study determined that the psychological skills training program increased the handball players\" self-efficacy and shot accuracy. Positive feedback strengthened the effect of the training even more on the self-efficacy beliefs and shot accuracy performance of the young athletes.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Social Sciences and Humanities; Sociology; KONAKLAMA, EĞLENCE, SPOR VE TURİZM; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); HOSPITALITY, LEISURE, SPORT & TOURISM; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Turizm, Eğlence ve Konaklama İşletmeciliği; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Tourism, Leisure and Hospitality Management; Social Sciences & Humanities; Psychological Skills; Positive Feedback; Self-Efficacy; Shot Accuracy; Training; PHYSICAL-EDUCATION; COACH FEEDBACK; PERCEPTIONS; PERFORMANCE; MOTIVATION